Oral Expression of Young People Caused by the Use of New Media - Filipan-Žignić, Blaženka; Legac, Vladimir; Sobo, Katica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
The authors want to explore the extent to which the elements of the language of new media (abbreviations, omission, dialectisms, vulgarisms, anglicisms, etc.) are present in the speech of young Croatians (100 secondary school students in their final years) in their conversations due to the influence of the language of new media. The results of the research have shown that young people use a large number of the elements of the language of new media in their mutual communication, but it is much less than in their written communication.